La médiation : une façon efficace de conserver de bonnes relations d’affaires - Roy, Serge (Assurances, 1996)
The following article is entitled "Mediation: an efficient way to maintain good business relations". The author introduces the subject by defining the major alternative dispute resolution processes, namely partnering, negotiation, conciliation, mediation, co-mediation, med/arb, mini-trial and arbitration. He then explains the advantages of mediation and the aspects to be cautious with. The article describes interest based negotiation, the role of the mediator, styles of mediation, when and how to go to mediation, the steps of the mediation process, the role of the legal counsel, real life cases and recent developments. At the end of the article, there is a sample of an agreement by which the parties may choose the mediation process, set the conditions of the mediation and appoint a mediator.